Infant gut microbiota colonization: influence of prenatal and postnatal factors, focusing on diet - Suárez-Martínez, Clara; Santaella-Pascual, Marina; Yagüe-Guirao, Genoveva; Martínez-Graciá, Carmen (Frontiers in Microbiology, 2023)
Maternal microbiota forms the first microbial inoculum and perinatal factors (diet and use of antibiotics during pregnancy) and/or neonatal factors, like intra partum antibiotics, gestational age and mode of delivery, all may contribute to influence microbial colonization. After birth, when the principal colonization occurs, the microbial diversity increases and converges toward a stable adultlike microbiota by the end of the first 3-5 years of life. But during the early life, gut microbiota can be disrupted by other postnatal factors like infant feeding mode, antibiotic usage, and various environmental factors (pets and siblings) generating a state of dysbiosis. Gut dysbiosis have been reported to increase the risk of necrotizing enterocolitis and some chronic diseases later in life, for example obesity, diabetes, cancer, allergies, and asthma. Therefore, understanding the impact of a correct maternal-to-infant microbial transfer and a good infant early colonization and maturation throughout life would reduce the risk of disease in early and late life. This paper reviews the published evidence on early-life gut microbiota development, as well as the different factors influencing its development before, at, and after birth, focusing on diet and nutrition during pregnancy and during the first months of life.